THE EFFECT OF PROBLEM BASED LEARNING STRATEGY TOWARD STUDENTS’ SPEAKING ABILITY AT THE FIRST GRADE OF SMAN 1 ENAM LINGKUNG - Ridho Angga Mulya SY; Aryuliva Adnan; Havid Ardi (Journal of English Language Teaching, 2013)
AbstrakThis study was to see the implementation of Problem Based Learning as one of strategies in learning descriptive text toward students speaking ability in describing people, things or places. It was done to the students at the first grade of X2 and X6 at SMAN 1 Enam Lingkung registered in 2012/2013. The data of the study were collected through tests. The findings of the study showed that experimental group taught by the problem based learning methods have better ability than control group which is taught by the conventional method. So, it can conclude that the used of Problem based learning in teaching descriptive text can improve students’ speaking ability in expressing description about people, things and places.Keyword: implementation, Problem Based Learning, speaking ability, descriptive